Habilidades sociales en el espectro autista - Bejarano Cajachagua, Cesia (2019)
This work is theoretical in nature. The purpose was to identify the characteristics of the social skills that a personhas autism spectrum and how these can be developed in it. We review the contributions of researchers as Reviere(1997), Melendez (2009) and the DSM-IV (2002), who think of autism as a pervasive developmental disorder ofneurological affects three interrelated specific functions, which are develop during the first 3 years of life, these are:social interaction, communication and language difficulty patterns of behavior, interests and activities restrictedrepetitive and stereotyped. And for understanding social skills social learning theories and vicar, which indicatethat the individual has the capacity to perceive, understand, decipher, and then respond to certain social stimuli ingeneral. We conclude that no one is restricted to develop these skills that really are vital to our adaptation in thecontext that is, in the same way a person belonging to the autistic spectrum may possess and develop as well as other“normal” social skill